Model tax convention on income and on capital: June 1998 condensed version - Organisation for Economic Co-operation and Development (OECD Publishing, 1998)
This 1998 edition of the Model Tax Convention: Condensed Version has been superceded by more recent editions. This publication is the third edition of the condensed version of another OECD publication entitled Model Tax Convention on Income and on.